2018
DOI: 10.1016/j.addbeh.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

The role of distress tolerance in the relationship between cognitive schemas and alcohol problems among college students

Abstract: Introduction The current study tested the role of distress tolerance in the relationship between three early maladaptive cognitive schemas (Abandonment, Defectiveness/Shame, and Insufficient Self-Control) and alcohol problems among college students (N = 364). Previous research suggests that maladaptive cognitive schemas may be a risk factor for alcohol-related problems. However, the mechanism underlying this association is unclear. One's tolerance for emotional distress may play an important role in understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
5
17
1
Order By: Relevance
“…Other studies have also found associations between specific EMS (e.g., defectiveness/shame, dependence/incompetence, abandonment/instability, and insufficient self-control) and depression (Hawke et al, 2011;Oliveira & Nobre, 2013). Several global studies of college student samples from various countries and ethnic groups have confirmed associations between general and/or specific EMS and depression with that demographic (Sigre-Leirós et al, 2013;Simons et al, 2018;Thimm, 2017).…”
Section: Depressionmentioning
confidence: 92%
“…Other studies have also found associations between specific EMS (e.g., defectiveness/shame, dependence/incompetence, abandonment/instability, and insufficient self-control) and depression (Hawke et al, 2011;Oliveira & Nobre, 2013). Several global studies of college student samples from various countries and ethnic groups have confirmed associations between general and/or specific EMS and depression with that demographic (Sigre-Leirós et al, 2013;Simons et al, 2018;Thimm, 2017).…”
Section: Depressionmentioning
confidence: 92%
“…Individuals with poor DT are more likely to assess unpleasant emotional or somatic states as being unacceptable (Wray et al, 2012) and use maladaptive regulatory strategies (R. M. Simons et al, 2018) to avoid or terminate these states. Alcohol use is one strategy that individuals can use to mitigate the distress caused by unpleasant emotional or somatic experiences; however, research on the association between DT and alcohol use behaviors among young adults who drink has produced mixed findings.…”
mentioning
confidence: 99%
“…Whereas some research has revealed a significant relationship between DT and alcohol use behaviors, other studies have produced mixed findings. R. M. Simons et al (2018) reported that, among a sample of college students, lower levels of DT were related to more alcohol-related negative consequences, but DT was not associated with total number of drinks consumed in a typical week. Other researchers have found that DT is relevant in explaining alcohol-related negative consequences only within specific populations of young adults (i.e., African American college students; Dennhardt & Murphy, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations